Strengthening Skills for Preparing Merdeka Curriculum Teaching Modules Phase F for MPLB Teachers in Semarang City - Raharjo, Teguh Hardi; Ismiyati; Wirawan, Arif Wahyu; Mulyanto, Asti Agustin Putri; Purwaningsih, Rika Aprilia (Indonesian Journal of Devotion and Empowerment, 2024)
Teachers are expected to be able to carry out learning in accordance with the merdeka curriculum, including the use of teaching modules in accordance with the provisions of the curriculum. Ideally, teachers can design teaching modules optimally. However, in reality, many teachers are not yet able to create teaching modules merdekaly according to the needs and situations in their learning environment. Several teachers stated that it required additional time, money and energy to compose teaching modules comprehensively, which became an obstacle in preparing teaching modules merdekaly. The Office Management and Business Services Skills Program (MPLB) in Phase F is not included in the Center of Excellence (PK) Vocational School program, part of the merdeka learning program. The aim of this service activity is to strengthen partners' skills in compiling merdeka curriculum teaching modules through several stages: socialization, training, mentoring and evaluation. This devotion was carried out for one week from June 26 to July 3, 2024 offline with 25 teacher participants at State Vocational School 2, Semarang City. The evaluation results show an increase in participants' abilities and skills in compiling Phase F teaching modules according to the existing learning environment.